2008
DOI: 10.1080/03009740801898608
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of serum TWEAK level to cytokine level, disease activity, and response to anti‐TNF treatment in patients with rheumatoid arthritis

Abstract: Serum levels of TWEAK were significantly elevated in patients with RA, and reflected disease activity and short-term response to etanercept treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
56
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 39 publications
4
56
0
Order By: Relevance
“…[16] However, little is known about the effect of anti-TnF-alpha on TWEAK expression. Park et al [8] reported that serum levels of TWEAK were significantly elevated in patients with RA, and indicated a short-lived response to anti-TnF-alpha. However, in anti-TnF-alpha non-responder patients, the serum TWEAK levels were reported to remain unchanged.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[16] However, little is known about the effect of anti-TnF-alpha on TWEAK expression. Park et al [8] reported that serum levels of TWEAK were significantly elevated in patients with RA, and indicated a short-lived response to anti-TnF-alpha. However, in anti-TnF-alpha non-responder patients, the serum TWEAK levels were reported to remain unchanged.…”
Section: Discussionmentioning
confidence: 99%
“…However, in anti-TnF-alpha non-responder patients, the serum TWEAK levels were reported to remain unchanged. [8] ın a recent study, TWEAK and its fibronectin (Fn) receptor were found to be expressed in the inflamed synovium of RA and psoriatic arthritis patients. of particular interest was the fact that TWEAK and Fn expression were unchanged after four weeks of anti-TnF-alpha treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to data showing TWEAK proinflammatory, proangiogenic, and proliferation-inducing effects in disease models in animals (5,(23)(24)(25) and association of pathway activation with human disease (21,22,(26)(27)(28), some published in vitro studies have shown that TWEAK induces apoptosis via upregulation of TNFa (29) or in combination with IFNg in a small number of tumor cell lines (8). In the absence of IFNg, apoptosis induction was modest (30) or required relatively high TWEAK concentrations (29).…”
Section: Introductionmentioning
confidence: 94%
“…Rather CD45 is a protein tyrosine kinase biomarker present on the precursor cell that may eventually differentiate into granulocytes, T-and B-cells, monocytes and thrombocytes. Another study showed that TWEAK levels were substantially elevated in the serum of RA patients and that serum TWEAK levels correlated with RA disease activity [32].…”
Section: Tweakmentioning
confidence: 99%